Effect of Low-Dose Antigen Exposure on Development of Immunity to Helicobacter pylori Infection in Mice - Radcliff, Fiona J. (American Society for Microbiology, 2001)
The effect of low-dose antigen exposure on the development of immunity to Helicobacter pylori infection was studied in outbred mice. Animals that were primed with a subinfectious number of H. pylori bacteria exhibited significantly lower bacterial loads after challenge with an infectious dose of pathogen (versus controls, P < 0.05).